2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854610
|View full text |Cite
|
Sign up to set email alerts
|

MIMO radar capability on powerful jammers suppression

Abstract: The problem of jammers suppression in colocated multipleinput multiple-output (MIMO) radar is considered. We resort to reduced dimension (RD) beamspace designs with robustness/adaptiveness to achieve the goal of efficient jammers suppression. Specifically, our RD beamspace techniques aim at designing optimal beamspace matrices based on reasonable tradeoffs between the desired in-sector source distortion and the powerful jammer (possibly in-sector) attenuation when conducting the jammers suppression. These desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Additionally, we increase the number of jammers to 5 and the clutter rank to 10. The five jamming signals have azimuth angles θ j = [0, 5,15,25,30] degrees and powers of 13dBW, and the total clutter-to-noise ratio is set to 13 dB. The SOI is assumed to have a power of 20dBW at the reciever and its azimuth is varied between 0 • to 30 • .…”
Section: Simulationmentioning
confidence: 99%
“…Additionally, we increase the number of jammers to 5 and the clutter rank to 10. The five jamming signals have azimuth angles θ j = [0, 5,15,25,30] degrees and powers of 13dBW, and the total clutter-to-noise ratio is set to 13 dB. The SOI is assumed to have a power of 20dBW at the reciever and its azimuth is varied between 0 • to 30 • .…”
Section: Simulationmentioning
confidence: 99%
“…It has been claimed that MIMO can handle hot clutter (which is barrage noise jammer signals received after reflection from the ground) whereas conventional arrays cannot [26,27]. This is not true, conventional arrays can handle hot clutter just as well as MIMO arrays can [3].…”
Section: Jammer and Clutter Suppressionmentioning
confidence: 99%
“…For instance, in Song, Willett, and Zhou (), it is shown that a distributed MIMO radar system can counter the deceptive jamming owing to the spatial diversity, where the antijamming capability is a feature of MIMO radar. Li et al () investigate the problem of jammers suppression in colocated MIMO radar, which is solved by utilizing the reduced dimension beamspace designs with adaptiveness to suppress jammers. Further, the robust beamforming for MIMO radar in the presence of powerful jamming signals is studied in Li et al (), and two minimum variance distortionless response type beamformers are proposed.…”
Section: Introductionmentioning
confidence: 99%